Discrete Abelian gauge theories for quantum simulations of QED. (6th July 2015) - Notarnicola, Simone; Ercolessi, Elisa; Facchi, Paolo; Marmo, Giuseppe; Pascazio, Saverio; Pepe, Francesco V
Abstract: We study a lattice gauge theory in Wilson's Hamiltonian formalism. In view of the realization of a quantum simulator for QED in one dimension, we introduce an Abelian model with a discrete gauge symmetry, approximating the U (1) theory for large n . We analyze the role of the finiteness of the gauge fields and the properties of physical states, that satisfy a generalized Gauss's law. We finally discuss a possible implementation strategy, that involves an effective dynamics in physical space.